What's in a word? Victims on 'victim'. Issue 2 (May 2018) - Fohring, Stephanie
Identifying as a victim of crime is a complex process involving both social and personal motivations. This paper utilises data gathered from victims of crime to examine how their thoughts, feelings and reactions to the victim label are influenced by societal stigma, and how this influence is mediated by personal beliefs and cognitive processes. It does this firstly by examining participants' thoughts and reactions to the word 'victim', where findings indicate a distinct disconnect between how an incident of crime is labelled and how a victim identifies themselves, suggesting an acknowledgement of the incident as wrong and illegal, but denial of victimhood. Secondly, key themes considered by participants to be characteristic of victimhood are identified. These include weakness as a core characteristic of victims, the fluidity of the state of victimhood and the importance of effective coping versus suffering.